Assessing Patient Care Indicators in a Tertiary Care Teaching Hospital in Bangladesh - Alam, MM; Parveen, F; Iqbal, MJU; Noor, N; Begum, SA (Bangladesh Medical Journal, 2014)
A cross-sectional descriptive study was carried out among individuals attending the Out Patient Department (OPD) of Medicine, Surgery and Gynaecology & Obstetrics from February 1, 2010 to April 30, 2010 in Sir Salimullah Medical College and Mitford Hospital, Dhaka, Bangladesh to see the patterns of drug dispensing using World Health Organization core patient care indicators. The result of the study showed that the overall average consultation time and dispensing time were too short (2.5 minutes and 30 seconds per patient respectively). Of the drugs prescribed, only 20.15% were actually dispensed, whereas no appropriate labeling (0%) was observed and 37.3% of patients knew how to administer drugs correctly after receiving the drugs from the dispenser. So the finding from current study shows a trend towards inappropriate dispensing practice. Hence, there is a need for effective intervention programme to encourage the physicians and dispensing pharmacists in promoting patient care as well as health care facilities. DOI: http://dx.doi.org/10.3329/bmj.v41i1.18776 Bangladesh Medical Journal 2012 Vol. 41 No. 1; 21-24